Decision-Making In Crisis: Insights From Hungarian SMES And Households During The Covid-19 Pandemic - Titanilla Oravecz; Éva Pólya; Zoltán Máté (Decision Making: Applications in Management and Engineering, 2025)
This study aims to explore the transformations in consumer behaviour in Hungary resulting from the COVID-19 pandemic and the corresponding responses by businesses. The research incorporated semi-structured, in-depth interviews conducted with Hungarian enterprises between late February and early March 2023. The participants comprised owner-managers of 25 domestic small and medium-sized enterprises (SMEs), whose insights offered an understanding of organisational adaptability and resilience during times of crisis. In preparation for the quantitative phase of consumer research, twelve focus group interviews were carried out in February 2023 with young adult participants. These discussions sought to understand consumer responses to the crisis, shifts in purchasing and consumption behaviours, the perceived impacts of the pandemic, their personal experiences, and potential coping mechanisms. Subsequently, in November 2023, a nationally representative survey was administered to Hungarian consumers aged 18 and above, aiming to assess the behavioural shifts triggered by the coronavirus pandemic during 2020–2021. Data gathered from 1,000 respondents were analysed using cross-tabulation (Pearson’s chi-square test) and correspondence analysis to identify the key determinants influencing consumers’ financial wellbeing and the extent to which newly formed shopping habits were retained. The principal outcome of the investigation indicates that, although the pandemic engendered widespread economic instability and altered consumption dynamics, individuals' subjective experiences of financial difficulty often exceeded the realities reflected in macroeconomic indicators. Resilience appeared to vary across demographic segments, with most behavioural adaptations occurring out of necessity rather than choice. These insights underscore the imperative for tailored public policy interventions to assist SMEs in navigating economic volatility. Such measures may include financial support mechanisms and initiatives promoting digital transformation. Moreover, fostering consumer confidence and stabilising market conditions through strategies such as adaptable tax policies and targeted stimulus programmes is essential. Investment in digital infrastructure and broader access to e-commerce platforms also emerges as a critical factor for enhancing long-term economic resilience and competitiveness.